Diffusion magnetic resonance imaging - Chew, Choon Guan. (2010)
This final year project titled “Diffusion Magnetic Resonance Imaging” is an exploratory assignment undertaken by the student to fulfil the requirement of a Bachelor degree in Electrical and Electronic Engineering. Magnetic Resonance Imaging is a popular imaging technique that is used to obtain body images for assessment. Diffusion weighted Imaging is a specialized technique which utilizes the nature of moving water molecules in the body to produce quality images as well. In this project, the focus is fixed on exploring and understanding of the principles and workings of DWI. Articles published by professionals were read and commented. In DWI, magnetic sequences are applied to measure water diffusion. One such sequence is known as the Stejskal and Tanner sequence, where applied gradients can be adjusted in terms of amplitude, duration and time interval between pulses. These three factors contribute to a parameter called the b-value, where it is chosen at different values and plotted against the logarithm of signal intensity to obtain a graph. ADC is the slope of the curve. The clinical applications of DWI are also being touched upon to relate the science of DWI to practical use in life. Two examples are stroke and tumor, where DWI can be used for their diagnosis. Areas with restricted diffusion correspond to high signal intensity for DWI and low ADC values. The problem of T2 shine through effect is also briefly discussed.